(untitled) (Advances in Military Technology, 2022)
The article considers a methodical approach to assessing the level of threat to the civilian population in the case of the use of small arms for shooting at unmanned aerial vehicles (UAVs). This approach is based on modeling the process of bullet flight in the vertical plane, based on the algorithm for determining the probability of accidental human impact, which allows, depending on the kinetic energy of the bullet, to calculate the probability of accidental death and probability of accidental injury. Based on the simulation, the indicators of the probability of human injuries depend on the angles of the shot, which allows to justify the restrictions when firing UAVs from small arms.